Clustered metabolic risk and leisure-time physical activity in adolescents: effect of dose?. Issue 2 (19th October 2010) - Pahkala, Katja; Heinonen, Olli J; Lagström, Hanna; Hakala, Paula; Hakanen, Maarit; Hernelahti, Miika; Ruottinen, Soile; Sillanmäki, Lauri; Rönnemaa, Tapani; Viikari, Jorma; Raitakari, Olli T; Simell, Olli
Abstract : Objectives: The authors studied the association of leisure-time physical activity (LTPA) with clustered and individual metabolic risk factors in adolescents taking into account diet and pubertal status. The authors also studied whether screen time was associated with clustered risk. Methods: Self-reported LTPA and screen time, lipids, lipoproteins, apolipoproteins, high-sensitivity C reactive protein, blood pressure, body mass index (BMI), pubertal status and diet were assessed in 13-year-old adolescents (n=542) participating in an atherosclerosis prevention study (Special Turku Coronary Risk Factor Intervention Project for Children). Activity groups were formed according to sex-specific LTPA index tertile cut-off points. BMI, high-density lipoprotein cholesterol (HDL-C), triglycerides and blood pressure comprised the cluster. Results: An increase in LTPA was associated with a decreased risk for clustered metabolic risk in girls. When sedentary and highly active adolescents were compared, an increase in LTPA decreased clustering of risk factors in boys as well. Little extra benefit on clustered risk was obtained by increasing LTPA from 30 MET h/week (eg, 4–5 h/week bicycling or playing soccer) to 50 MET h/week (eg, 7–8 h/week bicycling or playing soccer). LTPA was beneficially associated with BMI, HDL-C, systolic blood pressure and HDL-C/total cholesterol in girls and HDL-C in boys. Diet and pubertal status were similar in all activity groups. In girls, screen time >2 h/day was associated with an increased risk for clustered risk, independent of LTPA. Conclusion: Sedentary adolescents had an increased risk for clustered metabolic risk compared with physically more active peers. Only minor extra benefit was obtained when LTPA increased over 30 MET h/week. Focus in the prevention of clustered risk should especially be on avoiding sedentary lifestyle.